2022
DOI: 10.1111/jpi.12790
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the role of melatonin in human melanocyte physiology: A skin context perspective

Abstract: The evolutionarily ancient methoxyindoleamine, melatonin, has long perplexed investigators by its versatility of functions and mechanisms of action, which include the regulation of vertebrate pigmentation. Although first discovered through its potent skin‐lightening effects in amphibians, melatonin's role in human skin and hair follicle pigmentation and its impact on melanocyte physiology remain unclear. Synthesizing our limited current understanding of this role, we specifically examine its impact on melanoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 277 publications
2
41
1
Order By: Relevance
“…Melatonin (MT), an evolutionary ancient hormone, has been found in almost all organisms, ranging from animals, plants, and microorganisms [52,53]. Increasing studies have revealed that melanocytes can endogenously produce melatonin and its precursor serotonin (5 hydroxytryptamines: 5-HT) [54][55][56].…”
Section: Serotoninergic/melatoninergic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin (MT), an evolutionary ancient hormone, has been found in almost all organisms, ranging from animals, plants, and microorganisms [52,53]. Increasing studies have revealed that melanocytes can endogenously produce melatonin and its precursor serotonin (5 hydroxytryptamines: 5-HT) [54][55][56].…”
Section: Serotoninergic/melatoninergic Systemmentioning
confidence: 99%
“…Well established as the guardian of the genome and cellular and tissue in humans, melatonin exerts pleiotropic functions via melatonin receptor-dependent or non-receptor-dependent pathways such as potent antioxidative, free radical scavenging, anti-inflammatory, and mitochondrial protective activities [52,53]. It has been reported that melatonin and its metabolites, such as 6-hydroxymelatonin (6(OH)M), N1-acetyl-N2-formyl-5-methoxykynuramine (AFMK), can inhibit proliferation, pigmentation, and DNA synthesis in a dose-dependent manner in melanocytes [58].…”
Section: Serotoninergic/melatoninergic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in an open-label study of women and men with androgenetic alopecia, melatonin (33 ppm) topical application reduced the alopecia degree, and the TrichoScan technique showed a 29.2% increase in the hair count in 54.8% of patients after 3 months, and a 42.7% increase in 58.1% of patients after 6 months, demonstrating improvements in hair texture, decreased hair loss, and a reduction in seborrheic dermatitis, in safety and tolerant topical application of a cosmetic melatonin solution [ 117 ]. An exhaustive and recent revision of melatonin action in melanocyte physiology in humans and other mammals can be consulted [ 118 ].…”
Section: Melatoninmentioning
confidence: 99%
“…Therefore, melatonin was previously reported to be mainly synthesized in pinealocytes and then released into the bloodstream to reach central and peripheral organs for diverse roles. However, recent reports indicate that a majority of melatonin is synthesized in other tissues such as gut and skin rather than the pineal gland ( Yasmin et al, 2021 ; Sevilla et al, 2022 ), suggesting that it can also regulate biological activities by binding to its specific receptors in target tissues ( Shi et al, 2004 ; Isorna et al, 2009 ; Kuz’mina, 2020 ).…”
Section: Introductionmentioning
confidence: 99%